Bismuth activated full spectral double perovskite luminescence materials by excitation and valence control for future intelligent LED lighting. Issue 64 (13th July 2020) - Wei, Yi; Yang, Hang; Gao, Zhiyu; Xing, Gongcheng; Molokeev, Maxim S.; Li, Guogang
Abstract : Wide two-dimensional photoluminescence tuning and single-composition white emission with varied CCTs in La2 Mg1.14 Zr0.86 O6 :Bi 3+, Eu 3+ phosphors for future intelligent LED applications. Abstract : A novel La2 Mg1.14 Zr0.86 O6 :Bi 3+ double perovskite phosphor with excitation-induced blue/green photoluminescence tuning is reported. By designing Bi 3+ → Eu 3+ energy transfer, single-composition white light with wide-scale adjustable corrected color temperatures (CCTs) is successfully achieved. This work initiates a new insight to explore phosphors with excitation-induced photoluminescence tuning and wide CCT control for future intelligent LED lighting.